Smoking at the time of diagnosis and mortality in cancer patients: What benefit does the quitter gain?. Issue 8 (30th January 2017) - Tabuchi, Takahiro; Goto, Atsushi; Ito, Yuri; Fukui, Keisuke; Miyashiro, Isao; Shinozaki, Tomohiro
Abstract : Few studies have examined the association between smoking behavior (especially quitters) at the time of diagnosis and mortality among cancer patients. Our objective was to examine the benefits of quitting on all‐cause mortality among cancer patients. 30, 658 eligible cancer patients diagnosed between 1985 and 2009, identified by a hospital‐based cancer registry in Japan, were followed up for up to 10 years. We evaluated smoking behavior at cancer diagnosis (especially recent quitters vs . current smokers) in association with all‐cause mortality using Cox‐proportional hazards models and covariates‐adjusted survival curves. Risk of death was estimated to be reduced by 11% in recent quitters compared with current smokers. According to adjusted survival curves, median survival time was 8.25 years for recent quitters versus 7.18 years for current smokers, indicating an absolute difference of 1.07 year for a median survivor. Similarly, never and former smokers had 18% and 16% lower risk of death with 1.90 years and 1.77 years gained, respectively, compared with current smokers. In addition to former and never smokers, recent quitters showed consistently higher survival rates than current smokers during the 10‐year calendar period after diagnosis among cancer patients. Because recent quitters may be similar to patients who stop smoking shortly after cancer diagnosis in terms of smoking duration, the latter may be able to decrease their risk of death, suggesting that smoking cessation could be part of cancer care. Abstract : What's new? Tobacco smoking profoundly increases cancer risk, to the extent that quitting at any time is considered favorable to patient health. Just how significantly quitting smoking at the time of cancer diagnosis impacts mortality, however, is unclear. In this study, cancer patients who had recently quit smoking exhibited improved survival rates over patients who were smokers at the time of diagnosis. Among those who had recently quit, risk of death was reduced by 11 percent. Patients who had given up smoking just prior to diagnosis also gained one year of life compared with patients who were current smokers.